Numerical Treatment on Parabolic Singularly Perturbed Differential Difference Equation via Fitted Operator Scheme - Dagnachew Mengstie Tefera; Awoke Andargie Tiruneh; Getachew Adamu Derese (Abstract and Applied Analysis)
This paper proposes a new fitted operator strategy for solving singularly perturbed parabolic partial differential equation with delay on the spatial variable. We decomposed the problem into three piecewise equations. The delay term in the equation is expanded by Taylor series, the time variable is discretized by implicit Euler method, and the space variable is discretized by central difference methods. After developing the fitting operator method, we accelerate the order of convergence of the time direction using Richardson extrapolation scheme and obtained Oh2+k2 uniform order of convergence. Finally, three examples are given to illustrate the effectiveness of the method. The result shows the proposed method is more accurate than some of the methods that exist in the literature.